Assessing Port Service Quality on Customer Satisfaction: A Study of Dar Es Salaam Seaport, Tanzania - Msechu, Walter E.; Mashoke , Mary; Kahangwa, Strimius (Journal of Industrial Engineering & Management Research, 2025)
This study assesses the relationship between port service quality and customer satisfaction at Dar es Salaam Seaport, Tanzania. It focuses on three key variables of service quality, namely process, resource, and outcomes. The study employs a cross-sectional research design and adopts a quantitative research approach to collect and analyze data. A total of 201 respondents, comprising Clearing and Forwarding Agents and Shipping Agents, were selected using stratified random sampling to ensure proportional representation of participants. Data were gathered through structured questionnaires consisting of closed-ended questions measured on a 5-point Likert scale to facilitate statistical analysis. It applied the ROPMIS model as the theoretical framework to analyze how each variable of port service quality contributes to customer satisfaction. Descriptive statistics and multiple regression analysis were used to analyze the data. The findings revealed that all three variables, process, resources, and outcomes, had a positive and statistically significant influence on customer satisfaction. Among the three, outcomes had the strongest effect, followed by resource and process variables. Respondents identified challenges such as outdated infrastructure, slow cargo handling processes, and inadequate communication as key issues affecting satisfaction. The study concludes that improving service quality in terms of infrastructure, operational efficiency, and service consistency is essential for enhancing customer satisfaction at the port. Further research is recommended to compare customer satisfaction across Tanzanian ports, investigate the impact of digital technologies and pricing policies on service quality, and conduct qualitative studies with port staff to better understand internal operational challenges.